Biophysical study on the phase transition behaviour of biocompatible thermoresponsive polymer influenced by tryptophan-based amino acid ionic liquids. (16th July 2021) - Yadav, Ritu; Kahlon, Navjot K.; Kumar, Sumit; Devunuri, Nagaraju; Venkatesu, Pannuru
Abstract: Biocompatible thermoresponsive polymers are known to have numerous biomedical applications as they are capable of exhibiting a change in conformational states on changing the solution temperature. Poly(N-vinyl caprolactam) (PVCL) is one such polymer assessed frequently on conformational changes with biomolecules due to its amphiphilic nature. The goal of this work is to explore the impact of two tryptophan-based amino acid ionic liquids (AAILs), such as cholinium tryptophan ionic liquid ([CHO][Trp]IL) and tetraethylammonium tryptophan ionic liquid ([TEA][Trp]IL) on phase transition behaviour of aqueous PVCL solution. Biophysical techniques like steady-state fluorescence spectroscopy, thermal fluorescence spectroscopy, Fourier transform infrared (FTIR) spectroscopy, dynamic light scattering (DLS) and differential scanning calorimetry (DSC) are used to investigate the phase transition behaviour of aqueous PVCL-AAILs solution. The lower critical solution temperature (LCST) of PVCL was elevated by 4 and 2 °C on increase in the concentration from 1 to 5 mM of [CHO][Trp]IL and [TEA][Trp]IL, respectively. On comparing both AAILs, [CHO][Trp]IL has shown higher LCST (near to human physiological temperature) with aqueous PVCL solution than [TEA][Trp]IL due to its additional hydrogen bonding ability and its higher hydrophilicity compared to [TEA][Trp]IL. The structural functionalities of the cholinium cation like hydroxyl group and methyl substituents make it more advantageous than tetraethylammonium cation. This is the first time study on the phase transition behaviour of biocompatible thermoresponsive polymer PVCL influenced by tryptophan-based AAILs. These findings could be exploited for the development of biocompatible polymer to use in drug delivery and other biomedical applications. Graphical abstract: Image 1 Highlights: Amino acid ionic liquids (AAILs) were synthesized to monitor LCST of PVCL. LCST of PVCL in [CHO][Trp]IL was compared with PVCL in [TEA][Trp]IL. LCST of PVCL approaches human body temperature in case of [CHO][Trp]IL. DSC was deployed to study the heat changes of PVCL in AAILs. Hydrophilic character is provided by both [CHO][Trp]IL & [TEA][Trp]IL.